2021
DOI: 10.3390/ani11072005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Colostrum Quality and Quantity in Holstein Dairy Cattle

Abstract: The objective of this study was to conduct a large-scale investigation of colostrum composition and yield and an evaluation of factors affecting them. In this study, 1017 clinically healthy Holstein cows from 10 farms were used. The colostrum TS were measured using a digital Brix refractometer. Fat, protein and lactose content were determined using an infrared Milk Analyzer. Statistical analysis was conducted using a series of univariate general linear models. The mean (±SD) percentage of colostrum fat, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 42 publications
2
25
2
1
Order By: Relevance
“…In our observation, the colostrum Brix was 27.43% ± 2.42%, which is greater than that found by Turini et al [1] but similar to that reported by Sutter et al [2] and Soufleri et al [6]. The average reported here was well above the minimum suggested cutoff of 21% [3].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In our observation, the colostrum Brix was 27.43% ± 2.42%, which is greater than that found by Turini et al [1] but similar to that reported by Sutter et al [2] and Soufleri et al [6]. The average reported here was well above the minimum suggested cutoff of 21% [3].…”
Section: Discussionsupporting
confidence: 79%
“…Studies on the effect of collection time on colostrum quality often reported inconclusive results. For example, in the study by Sutter et al [2], cows that calved during the night (from 22.00 to 6.00) showed decreased colostrum Brix% compared to dams delivering during the day, while Soufleri et al [6] reported a slight decrease (1 Brix%) in colostrum collected 6 h after parturition. Lessler et al [26] and Van Keulen et al [8] found no difference, but in the latter case the authors compared the colostrum of dams milked within 12 h after calving and those milked from 18 to 24 h later and some cows from this group were also suckled.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations